English Language Teaching in Rural Areas: A New Challenge for English Language Teachers in Colombia (2016)
Most English teachers in Colombia are reluctant to work in rural schools due to several challenges that they may encounter. The purpose of this article, which is based on the results of research studies conducted in Boyacá and Santander (Colombia) about English teaching in rural areas, is to show some of the reasons why teachers do not select a job in rural zones. It also suggests some strategies to overcome these issues. Finally, the authors discuss some of the implications for teachers and stakeholders.